Effect of nut meg (Myristica fragrans) oiJ extract on testicular function in mice exposed to oxidative stress - Abdul kreem Ismail; Rafeh Ayoub (College of Education for Pure Sciences, 2007)
nut meg (Myristica fragrans) has been mentioned in ancient medicine to be beneficial in the managment of male sexual disorders. The present study is to evaluate the nut meg oil extract on testicular functions in mice exposed to 1% hydrogen peroxide for 21 days. Oral administration of nut meg oil extract at adose of 250 mg/kg produced asignificant decrease in testis weight and sperm count and percentage of viable and normal sperm as compared to hydrogen peroxide treated group. Oral administration of nut meg oil extract at 500 mg/kg dose produced a highly significant decrease in weight of testis and sperm count and percentage of viable and normal sperm as compared to hydrogen peroxide treated group. Also the mean number of spermatogonia reduced to a significant level as compared to hydrogen peroxide treated group and controL The present results suggest that nut meg popularly consumed as food and may contain some active principles with anti oxidant properties. However high doses of 250 or 500 mg/kg could be very toxic to the testis.